Protective Effects of Acetone Extract of Portulaca oleracea L. on Liver Histopathology in Hypoxia-Induced Sprague-Dawley Rats - Maliza, Rita; Syaidah, Rahimi; Setiawan, Haris; Galih Yatalaththov, Febriofca; Yashiro, Takashi; Arya, Bramadi; Aini, Wardatul (Biota, 2026)
Hypoxia, a condition characterized by insufficient oxygen supply, can cause tissue damage in vital organs, including the liver. The liver is particularly vulnerable to hypoxic injury, which may result in impaired function and hepatocyte death. Purslane (Portulaca oleracea L.) is known for its antioxidant properties, largely attributed to its flavonoid content, which can inhibit the production of reactive oxygen species (ROS). This experimental study aimed to evaluate the effects of acetone extracts of purslane herb on hepatic histopathological changes in hypoxia-induced rats. Five experimental groups were established, each consisting of six rats (n = 6): normal control (N), hypoxia (H), hypoxia treated with dexamethasone (H+DEXA), hypoxia treated with purslane extract at 150 mg/kg body weight (HP1), and hypoxia treated with purslane extract at 300 mg/kg body weight (HP2). Purslane extract was prepared using the acetone maceration method. Hypoxia was induced by exposing rats to a gas mixture of 10% O₂ and 90% N₂ for 10 consecutive days. Liver tissues were processed using paraffin embedding and stained with hematoxylin–eosin for histopathological evaluation, focusing on hepatocyte necrosis, inflammatory cell infiltration, and hemorrhage. Statistical analysis was performed using one-way analysis of variance (ANOVA) followed by Duncan’s post hoc test. The results showed that the 300 mg/kg dose of purslane extract significantly reduced hepatocyte necrosis (35.33 ± 2.52 cells), inflammatory cell infiltration area (2488.51 ± 112.82 µm²), and hemorrhage area (1031.10 ± 17.38 µm²) compared with the hypoxia group (p < 0.05). In conclusion, acetone extracts of purslane demonstrated significant hepatoprotective effects in hypoxia-induced rats, suggesting their potential as a natural therapeutic agent for the management of hypoxia-related liver injury.